THE AXIOLOGY OF ADMINISTRATIVE LAW FUNDAMENTAL ISSUES - Bartosz Majchrzak (Zeszyty Prawnicze)
This article addresses the nature, role, and catalogue of values in administrative law. I present a reconstruction of the basic concepts associated with this branch of the law; I describe the legal constructions which are the sources for the decoding of the values in administrative law; and I classify these values according to a set of criteria I have adopted. In addition I remark on the relations between particular values in the provisions of administrative law and the mechanisms to be applied to resolve collisions in the event of conﬂicting values.